Environment-friendly chemical-resistant high-pressure hydrogen transmission and storage coating and preparation method thereof

The hydrogen coating composition, featuring modified cellulose nanocrystals and a composite filler, effectively addresses hydrogen embrittlement by blocking hydrogen diffusion and enhancing mechanical strength, ensuring safe and efficient hydrogen storage and transport.

CN119662104AActive Publication Date: 2025-03-21SHANGHAI TIAN YANG STEEL TUBE

Patent Information

Application Number
CN202411907715.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Hydrogen gas faces challenges in transportation and storage due to its high permeability and diffusivity through metal materials, leading to 'hydrogen embrittlement' which reduces material strength and poses safety risks, necessitating the development of effective barrier layers to prevent hydrogen penetration.

Method used

A high-pressure hydrogen coating composition comprising water-based polyurethane emulsion, modified cellulose nanocrystals, and a composite filler material, including sodium montmorillonite and zinc oxide, with surface modification using alkyl quaternary ammonium compounds and fatty acids to enhance compatibility and block hydrogen diffusion.

Benefits of technology

The coating significantly improves hydrogen barrier performance, mechanical strength, and chemical stability, forming a dense and stable layer that effectively prevents hydrogen leakage and embrittlement, while being environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204797280000101
    Figure BDA0005204797280000101
  • Figure BDA0005204797280000111
    Figure BDA0005204797280000111
Patent Text Reader

Abstract

The invention relates to an environment-friendly chemical-resistant high-pressure hydrogen transmission and storage coating and a preparation method thereof, and belongs to the technical field of hydrogen permeation resistance. Montmorillonite is modified by methyl dodecyl bis (hydroxyethyl) ammonium chloride, and zirconium oxide is deposited on the surface of the montmorillonite to form the composite filler. According to the composite filler, the compatibility and dispersity with a polymer matrix are remarkably improved, hydrogen molecules are effectively adsorbed and anchored by using oxygen vacancies in zirconium dioxide, and diffusion and permeation of hydrogen are further hindered. The cellulose nanocrystals are modified through stearic acid, hydrophobic groups are successfully introduced, the agglomeration phenomenon of the cellulose nanocrystals is remarkably weakened, and the dispersity and compatibility of the cellulose nanocrystals in a waterborne polyurethane emulsion are improved. The modified cellulose nanocrystals provide excellent hydrogen resistance, chemical resistance and mechanical strength for the coating, a highly compact structure is formed, hydrogen leakage is effectively prevented, pores and defects of the coating are reduced, and compactness and hydrogen resistance of the coating are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen penetration resistance, and relates to an environmentally friendly, chemically resistant, high-pressure hydrogen transmission and storage coating and a preparation method thereof. Background Art

[0002] As one of the most abundant elements in nature, hydrogen's unique energy value is increasingly attracting global attention. Hydrogen can be produced efficiently by using renewable energy to electrolyze water, and the energy density produced by its combustion is extremely high. At the same time, this process does not produce greenhouse gases or other harmful substances, showing great potential as a clean energy carrier in the future. However, despite the broad application prospects of hydrogen energy, its transportation and storage in practical applications face severe technical challenges.

[0003] Due to their extremely small diameter, hydrogen atoms have extremely high permeability and diffusivity compared to metal atoms, which means that during the transmission and storage of hydrogen, hydrogen atoms can easily penetrate metal hydrogen pipelines and hydrogen storage container walls, causing "hydrogen embrittlement". Hydrogen embrittlement not only significantly changes the mechanical properties of metal materials, reducing their strength and toughness, but also may cause sudden fracture of materials in extreme cases, posing a serious threat to the safety and reliability of hydrogen energy systems. In addition, once the hydrogen embrittlement effect is formed inside the material, it is an irreversible process and its impact cannot be eliminated by subsequent repair methods. In order to slow down the penetration and diffusion of hydrogen in metals, preparing a hydrogen barrier coating on the surface of the material has become an effective means to delay or prevent hydrogen from penetrating into the material and prevent hydrogen embrittlement. Therefore, it is of great significance to develop a new type of hydrogen barrier coating that is both environmentally friendly and has excellent chemical resistance. Summary of the invention

[0004] The object of the present invention is to provide an environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating and a preparation method thereof, which has the characteristics of excellent hydrogen resistance and chemical resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating, the formula of the high-pressure hydrogen transport and storage coating is as follows: by weight, 60 to 80 parts of aqueous polyurethane emulsion, 30 to 40 parts of modified cellulose nanocrystals, 5 to 15 parts of composite filler, 5 to 7 parts of dispersant, 2 to 3 parts of cross-linking agent, 1 to 2 parts of film-forming aid,

[0007] Wherein, the preparation method of the composite filler is as follows:

[0008] S1-1: 10 to 20 parts by weight of nano-sized sodium montmorillonite is added to 280 to 300 parts by weight of deionized water, and stirred at 40° C. for 1.5 hours to obtain a suspension A;

[0009] S1-2: 5 to 10 parts by weight of methyl dodecyl bis(hydroxyethyl)ammonium chloride are added to 90 to 100 parts by weight of deionized water, and ultrasonicated for 30 minutes, and then 1 to 2 parts by weight of hydrochloric acid solution are added, and ultrasonicated for 30 minutes to obtain solution B;

[0010] S1-3: Solution B was added dropwise to suspension A, stirred at 80°C for 1.5 h, filtered and washed with 70% ethanol solution, and dried at 100°C for 12 h to obtain powder C;

[0011] S1-4: 10 to 20 parts by weight of zirconium isopropoxide and 70 to 90 parts by weight of a 50% ethanol solution are mixed, powder C is added, refluxed at 60°C for 1 hour, washed with deionized water and anhydrous ethanol, calcined in a muffle furnace for 1 hour at a calcination temperature of 400 to 600°C, and then ball-milled in a ball mill for 1.5 hours at a ball mill speed of 400 to 500 r / min to obtain the composite filler.

[0012] Further, the preparation method of modified cellulose nanocrystals is as follows:

[0013] S2-1: adding 20 to 40 parts by weight of cellulose nanocrystals to 60 to 80 parts by weight of deionized water, and dispersing the mixture at a stirring speed of 800 to 1000 r / min for 30 minutes to obtain a suspension D;

[0014] S2-2: Add 3 to 5 parts by weight of stearic acid to 20 to 30 parts by weight of anhydrous ethanol, and stir at 80 to 90° C. for 1 hour to obtain solution E;

[0015] S2-3: The suspension D and the solution E are mixed, stirred at 70-80° C. for 1.5 h, washed with deionized water and anhydrous ethanol, and freeze-dried in a freeze dryer to obtain the modified cellulose nanocrystals.

[0016] Furthermore, the dispersant is one of polyethylene glycol and polypropylene glycol.

[0017] Furthermore, the cross-linking agent is one or more of the silane coupling agents KH550, KH560 and KH570.

[0018] Furthermore, the concentration of the hydrochloric acid solution in S1-2 is 6M.

[0019] Furthermore, according to the environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating according to claim 1, it is characterized in that the dripping speed of solution B in S1-3 is 1 mL / min.

[0020] Furthermore, the freeze-drying temperature of the freeze-drying machine in S2-3 is -30°C, and the freeze-drying time is 12 hours.

[0021] Furthermore, the film-forming aid is alcohol ester 12.

[0022] A method for preparing an environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating, the specific steps of the preparation method are as follows:

[0023] S9-1: According to the formula, the aqueous polyurethane emulsion, modified cellulose nanocrystals, composite filler, dispersant, crosslinking agent and film-forming aid were mixed for 30 minutes to obtain a coating;

[0024] S9-2: The steel pipe is added to a 75% by mass ethanol solution and ultrasonicated for 20 minutes, placed in a 60°C vacuum drying oven for 12 hours, and then the surface of the steel pipe is subjected to high-energy shot peening to nano-crystallize the surface, thereby obtaining a pretreated steel pipe;

[0025] S9-3: Spin-coat the coating on the inside of the pretreated steel pipe, and obtain the coating after drying.

[0026] An application of an environmentally friendly, chemically resistant, high-pressure hydrogen transmission and storage coating, wherein the coating can be applied to hydrogen transmission pipelines and hydrogen storage cylinders.

[0027] Polymer hydrogen barrier is based on the principle of "like dissolves like". Hydrogen is a non-polar molecule and therefore tends to dissolve in non-polar solutions. When polymer materials have a very dense structure, they will strictly limit the diffusion of hydrogen. Cellulose nanocrystals, as a nanoscale material derived from biomass, have the characteristics of high strength, high aspect ratio, biodegradability and good hydrogen barrier properties. However, the large specific surface area and abundant hydrophilic hydroxyl groups on the surface of cellulose nanocrystals, coupled with strong intermolecular hydrogen bonding, make it easy to agglomerate in the organic polymer matrix, resulting in poor dispersibility and compatibility. Cellulose nanocrystals are also sensitive to water and lose their isolation properties when humidity rises. Stearic acid, as a long-chain fatty acid with both lipophilic long carbon chains and hydrophilic carboxyl groups, can undergo esterification reaction with the hydroxyl groups on the surface of cellulose nanocrystals, thereby successfully introducing hydrophobic groups on the surface of cellulose nanocrystals. This modification not only reduces the surface energy of cellulose nanocrystals, but also significantly changes the wetting properties of their surface, thereby enhancing the interaction between cellulose nanocrystals and aqueous polyurethane emulsions. After being modified with stearic acid, the number of hydroxyl groups on the surface of cellulose nanocrystals is significantly reduced, effectively weakening the agglomeration phenomenon, and thus significantly improving the dispersibility in the aqueous polyurethane emulsion, effectively promoting the full mixing of cellulose nanocrystals and aqueous polyurethane emulsion, and enhancing the compatibility between the two. In addition, the modified cellulose nanocrystals provide the coating with good chemical resistance and mechanical strength, allowing the coating to form a highly compact structure, effectively preventing hydrogen leakage, and helping to reduce pores and defects in the coating, thereby further improving the density and hydrogen barrier properties of the membrane.

[0028] As a cationic surfactant, methyl dodecyl dihydroxyethyl ammonium chloride can exchange with cations between sodium montmorillonite layers, thereby increasing the interlayer spacing and surface properties of montmorillonite, which helps to improve the compatibility of montmorillonite with the polymer matrix, promote dispersibility, and further enhance the hydrogen barrier performance of the coating. In addition, zirconium dioxide is deposited on montmorillonite to form a composite filler. Zirconium dioxide contains oxygen vacancies. These oxygen vacancies can adsorb and anchor hydrogen molecules as defect sites, thereby further hindering the diffusion and penetration of hydrogen. This composite filler not only promotes the formation of a more compact and stable structure of the coating, effectively blocking the penetration of hydrogen, but also provides additional mechanical support and enhances the overall strength of the coating; at the same time, the composite filler maintains good chemical stability and can maintain stable performance in various harsh environments. In addition, the composite filler can effectively combine with modified cellulose nanocrystals to form a good interface interaction, further improve the density of the coating, and reduce the permeation channels of gas and liquid. Montmorillonite and zirconium dioxide in the composite filler are both environmentally friendly materials, will not cause harm to the environment, and are in line with the concept of sustainable development.

[0029] The surface of the steel pipe is subjected to high-energy shot peening to nano-size its surface. The coating can more effectively penetrate into the tiny gaps and pores on the surface of the steel pipe, which is conducive to the coating penetrating into the surface of the steel pipe to form a mechanical interlocking structure, greatly improving the bonding strength between the coating and the steel pipe.

[0030] Beneficial effects of the present invention:

[0031] (1) Montmorillonite was modified by methyl dodecyl bis(hydroxyethyl) ammonium chloride and zirconium oxide was deposited on the surface to form a composite filler, which significantly improved the compatibility and dispersibility of the composite filler with the polymer matrix. The oxygen vacancies in zirconium dioxide were used as defect sites to effectively adsorb and anchor hydrogen molecules, further hindering the diffusion and penetration of hydrogen. It also provided additional mechanical support and chemical resistance, thereby enhancing the overall strength of the coating.

[0032] (2) Cellulose nanocrystals were modified with stearic acid and hydrophobic groups were successfully introduced, which effectively weakened the agglomeration of cellulose nanocrystals and significantly improved the dispersibility and compatibility of cellulose nanocrystals in aqueous polyurethane emulsions, thereby enhancing the overall performance of the coating material. The modified cellulose nanocrystals provide the coating with excellent hydrogen barrier properties, chemical resistance, and mechanical strength, forming a highly compact structure that effectively prevents hydrogen leakage and reduces the pores and defects in the coating, further improving the density and hydrogen barrier properties of the coating. DETAILED DESCRIPTION

[0033] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0034] In the embodiments of the present invention and the comparative examples:

[0035] Waterborne polyurethane emulsion: purchased from Shanghai Yihe Biotechnology Co., Ltd.;

[0036] Cellulose nanocrystals: purchased from Shenzhen Huanuo Biotechnology Co., Ltd.;

[0037] Stearic acid: purchased from Hunan Ruhong Pharmaceutical Co., Ltd.

[0038] Anhydrous ethanol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0039] Sodium montmorillonite: purchased from Lingyuan Beibiansen Biotechnology Co., Ltd.;

[0040] Methyl dodecyl bis(hydroxyethyl)ammonium chloride: purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.;

[0041] Zirconium isopropoxide: purchased from Shanghai Myrel Biochemical Technology Co., Ltd.;

[0042] Polyethylene glycol: purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.;

[0043] Polypropylene glycol: purchased from Shanghai Baoyang Baoxin Biotechnology Co., Ltd.;

[0044] Silane coupling agents KH550, KH560, and KH570 were purchased from Nanjing Quanxi New Materials Co., Ltd.

[0045] Alcohol ester 12: purchased from Shanghai Biyang Industrial Co., Ltd.

[0046] Example 1

[0047] An environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating. The formula 1 of the high-pressure hydrogen transport and storage coating is as follows: in parts by weight, 70 parts of aqueous polyurethane emulsion, 35 parts of modified cellulose nanocrystals, 10 parts of composite filler, 6 parts of polyethylene glycol, 2.5 parts of silane coupling agent KH550, and 121.5 parts of alcohol ester.

[0048] Wherein, the preparation method of the composite filler is as follows:

[0049] S1-1: 15 parts by weight of nano-sized sodium montmorillonite was added to 290 parts by weight of deionized water, and the mixture was stirred at 40° C. for 1.5 h to obtain a suspension A;

[0050] S1-2: 8 parts by weight of methyl dodecyl bis(hydroxyethyl)ammonium chloride were added to 95 parts by weight of deionized water, and ultrasonicated for 30 minutes, and then 1.5 parts by weight of 6M hydrochloric acid solution were added, and ultrasonicated for 30 minutes to obtain solution B;

[0051] S1-3: Solution B was added dropwise to suspension A at a rate of 1 mL / min, stirred at 80°C for 1.5 h, filtered and washed with 70% ethanol solution, and dried at 100°C for 12 h to obtain powder C;

[0052] S1-4: 15 parts by weight of zirconium isopropoxide and 80 parts by weight of 50% ethanol solution are mixed, powder C is added, refluxed at 60°C for 1 hour, washed with deionized water and anhydrous ethanol, calcined in a muffle furnace for 1 hour at a calcination temperature of 500°C, and then ball-milled in a ball mill for 1.5 hours at a ball mill speed of 450 r / min to obtain the composite filler.

[0053] The preparation method of modified cellulose nanocrystals is as follows,

[0054] S2-1: 30 parts by weight of cellulose nanocrystals were added to 70 parts by weight of deionized water, and dispersed at a stirring speed of 900 r / min for 30 min to obtain a suspension D;

[0055] S2-2: 4 parts by weight of stearic acid were added to 25 parts by weight of anhydrous ethanol, and the mixture was stirred at 85° C. for 1 h to obtain a solution E;

[0056] S2-3: The suspension D and the solution E were mixed, stirred at 75° C. for 1.5 h, washed with deionized water and anhydrous ethanol, and freeze-dried in a -30° C. freeze dryer for 12 h to obtain the modified cellulose nanocrystals.

[0057] A method for preparing an environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating, the specific steps of the preparation method are as follows:

[0058] S9-1: According to formula 1, water-based polyurethane emulsion, modified cellulose nanocrystals, composite filler, polyethylene glycol, silane coupling agent KH550 and alcohol ester 12 were mixed for 30 minutes to obtain a coating;

[0059] S9-2: The steel pipe is added to a 75% by mass ethanol solution and ultrasonicated for 20 minutes, placed in a 60°C vacuum drying oven for 12 hours, and then the surface of the steel pipe is subjected to high-energy shot peening to nano-crystallize the surface, thereby obtaining a pretreated steel pipe;

[0060] S9-3: Spin-coat the coating on the inside of the pretreated steel pipe, and obtain the coating after drying, with a coating thickness of 50 μm.

[0061] Example 2

[0062] An environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating. The formula 2 of the high-pressure hydrogen transport and storage coating is as follows: in parts by weight, 60 parts of aqueous polyurethane emulsion, 30 parts of modified cellulose nanocrystals, 5 parts of composite filler, 5 parts of polypropylene glycol, 2 parts of silane coupling agent KH560, 121 parts of alcohol ester,

[0063] Wherein, the preparation method of the composite filler is as follows:

[0064] S1-1: 10 parts by weight of nano-sized sodium montmorillonite was added to 280 parts by weight of deionized water, and the mixture was stirred at 40° C. for 1.5 h to obtain a suspension A;

[0065] S1-2: 5 parts by weight of methyl dodecyl bis(hydroxyethyl)ammonium chloride were added to 90 parts by weight of deionized water, and ultrasonicated for 30 minutes, and then 1 part by weight of 6M hydrochloric acid solution was added, and ultrasonicated for 30 minutes to obtain solution B;

[0066] S1-3: Solution B was added dropwise to suspension A at a rate of 1 mL / min, stirred at 80°C for 1.5 h, filtered and washed with 70% ethanol solution, and dried at 100°C for 12 h to obtain powder C;

[0067] S1-4: 10 parts by weight of zirconium isopropoxide and 70 parts by weight of 50% ethanol solution are mixed, powder C is added, refluxed at 60°C for 1 hour, washed with deionized water and anhydrous ethanol, calcined in a muffle furnace for 1 hour at a calcination temperature of 400°C, and then ball-milled in a ball mill for 1.5 hours at a ball mill speed of 400 r / min to obtain the composite filler.

[0068] The preparation method of modified cellulose nanocrystals is as follows,

[0069] S2-1: 20 parts by weight of cellulose nanocrystals were added to 60 parts by weight of deionized water, and dispersed at a stirring speed of 800 r / min for 30 min to obtain a suspension D;

[0070] S2-2: 3 parts by weight of stearic acid were added to 20 parts by weight of anhydrous ethanol, and the mixture was stirred at 80° C. for 1 h to obtain a solution E;

[0071] S2-3: The suspension D and the solution E were mixed, stirred at 70° C. for 1.5 h, washed with deionized water and anhydrous ethanol, and freeze-dried in a -30° C. freeze dryer for 12 h to obtain the modified cellulose nanocrystals.

[0072] A method for preparing an environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating, the specific steps of the preparation method are as follows:

[0073] S9-1: According to formula 2, water-based polyurethane emulsion, modified cellulose nanocrystals, composite filler, polypropylene glycol, silane coupling agent KH560 and alcohol ester 12 were mixed for 30 minutes to obtain a coating;

[0074] S9-2: The steel pipe is added to a 75% by mass ethanol solution and ultrasonicated for 20 minutes, placed in a 60°C vacuum drying oven for 12 hours, and then the surface of the steel pipe is subjected to high-energy shot peening to nano-crystallize the surface, thereby obtaining a pretreated steel pipe;

[0075] S9-3: Spin-coat the coating on the inside of the pretreated steel pipe, and obtain the coating after drying, with a coating thickness of 50 μm.

[0076] Example 3

[0077] An environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating. The formula 3 of the high-pressure hydrogen transport and storage coating is as follows: in parts by weight, 80 parts of aqueous polyurethane emulsion, 40 parts of modified cellulose nanocrystals, 15 parts of composite filler, 7 parts of polyethylene glycol, 3 parts of silane coupling agent KH570, 122 parts of alcohol ester,

[0078] Wherein, the preparation method of the composite filler is as follows:

[0079] S1-1: 20 parts by weight of nano-sized sodium montmorillonite was added to 300 parts by weight of deionized water, and the mixture was stirred at 40° C. for 1.5 h to obtain a suspension A;

[0080] S1-2: 10 parts by weight of methyl dodecyl bis(hydroxyethyl)ammonium chloride were added to 100 parts by weight of deionized water, and ultrasonicated for 30 minutes, and then 2 parts by weight of 6M hydrochloric acid solution were added, and ultrasonicated for 30 minutes to obtain solution B;

[0081] S1-3: Solution B was added dropwise to suspension A at a rate of 1 mL / min, stirred at 80°C for 1.5 h, filtered and washed with 70% ethanol solution, and dried at 100°C for 12 h to obtain powder C;

[0082] S1-4: Mix 20 parts by weight of zirconium isopropoxide and 90 parts by weight of 50% ethanol solution, add powder C, reflux at 60°C for 1 hour, wash with deionized water and anhydrous ethanol, place in a muffle furnace for 1 hour, the calcination temperature is 600°C, and then place in a ball mill for 1.5 hours at a ball mill speed of 500r / min to obtain the composite filler.

[0083] The preparation method of modified cellulose nanocrystals is as follows,

[0084] S2-1: 40 parts by weight of cellulose nanocrystals were added to 80 parts by weight of deionized water, and dispersed at a stirring speed of 1000 r / min for 30 min to obtain a suspension D;

[0085] S2-2: 5 parts by weight of stearic acid were added to 30 parts by weight of anhydrous ethanol, and stirred at 90° C. for 1 h to obtain solution E;

[0086] S2-3: The suspension D and the solution E were mixed, stirred at 80° C. for 1.5 h, washed with deionized water and anhydrous ethanol, and freeze-dried in a -30° C. freeze dryer for 12 h to obtain the modified cellulose nanocrystals.

[0087] A method for preparing an environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating, the specific steps of the preparation method are as follows:

[0088] S9-1: According to formula 3, water-based polyurethane emulsion, modified cellulose nanocrystals, composite filler, polyethylene glycol, silane coupling agent KH570 and alcohol ester 12 were mixed for 30 minutes to obtain a coating;

[0089] S9-2: The steel pipe is added to a 75% by mass ethanol solution and ultrasonicated for 20 minutes, placed in a 60°C vacuum drying oven for 12 hours, and then the surface of the steel pipe is subjected to high-energy shot peening to nano-crystallize the surface, thereby obtaining a pretreated steel pipe;

[0090] S9-3: Spin-coat the coating on the inside of the pretreated steel pipe, and obtain the coating after drying, with a coating thickness of 50 μm.

[0091] Comparative Example 1

[0092] The cellulose nanocrystals were not modified, and the remaining steps were consistent with those in Example 1.

[0093] Comparative Example 2

[0094] In the preparation of the composite filler, zirconium isopropoxide was not added, and the remaining steps were consistent with those in Example 1.

[0095] Comparative Example 3

[0096] No composite filler was added, and the remaining steps were the same as those in Example 1.

[0097] Comparative Example 4

[0098] No modified cellulose nanocrystals were added, and the remaining steps were consistent with those in Example 1.

[0099] The hydrogen permeability coefficient of the coatings prepared in the examples and comparative examples was measured according to GB / T 42610-2023 standard, the test pressure was 1.15 times the nominal working pressure of the gas cylinder (70 MPa), and the measurement temperature was 15°C;

[0100] The adhesion of the coatings prepared in the examples and comparative examples was measured according to GB / T 23257 standard, with the test temperature being 75° C. and the test time being 48 h.

[0101] The experimental data are summarized in the following table:

[0102]

[0103] It can be seen from the data of the examples and comparative examples that the coating obtained by compounding the filler obtained by modifying the cellulose nanocrystals with stearic acid, montmorillonite and zirconium oxide, the aqueous polyurethane emulsion and other additives has good substrate adhesion and hydrogen barrier properties.

[0104] The chemical resistance of the coating obtained in Example 1 was tested, and the experimental data are summarized in the following table:

[0105]

[0106] Note: Performance of coating after exposure in container for 18 months;

[0107] G = excellent, L = good.

[0108] From the data in the above table, it can be seen that the coating obtained by compounding the filler obtained by modifying cellulose nanocrystals with stearic acid, montmorillonite and zirconium oxide, and the aqueous polyurethane emulsion and other additives has excellent chemical resistance and shows excellent stability to most chemical reagents.

[0109] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. An environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating, characterized in that: The formula of the high-pressure hydrogen transport and storage coating is as follows: in parts by weight, 60 to 80 parts of aqueous polyurethane emulsion, 30 to 40 parts of modified cellulose nanocrystals, 5 to 15 parts of composite filler, 5 to 7 parts of dispersant, 2 to 3 parts of crosslinking agent, 1 to 2 parts of film-forming aid, Wherein, the preparation method of the composite filler is as follows: S1-1: 10 to 20 parts by weight of nano-sized sodium montmorillonite is added to 280 to 300 parts by weight of deionized water, and stirred at 40° C. for 1.5 hours to obtain a suspension A; S1-2: 5 to 10 parts by weight of methyl dodecyl bis(hydroxyethyl)ammonium chloride are added to 90 to 100 parts by weight of deionized water, and ultrasonicated for 30 minutes, and then 1 to 2 parts by weight of hydrochloric acid solution are added, and ultrasonicated for 30 minutes to obtain solution B; S1-3: Solution B was added dropwise to suspension A, stirred at 80°C for 1.5 h, filtered and washed with 70% ethanol solution, and dried at 100°C for 12 h to obtain powder C; S1-4: 10 to 20 parts by weight of zirconium isopropoxide and 70 to 90 parts by weight of a 50% ethanol solution are mixed, powder C is added, refluxed at 60°C for 1 hour, washed with deionized water and anhydrous ethanol, calcined in a muffle furnace for 1 hour at a calcination temperature of 400 to 600°C, and then ball-milled in a ball mill for 1.5 hours at a ball mill speed of 400 to 500 r / min to obtain the composite filler.

2. The environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating according to claim 1, characterized in that: The preparation method of the modified cellulose nanocrystals is as follows: S2-1: adding 20 to 40 parts by weight of cellulose nanocrystals to 60 to 80 parts by weight of deionized water, and dispersing the mixture at a stirring speed of 800 to 1000 r / min for 30 minutes to obtain a suspension D; S2-2: Add 3 to 5 parts by weight of stearic acid to 20 to 30 parts by weight of anhydrous ethanol, and stir at 80 to 90° C. for 1 hour to obtain solution E; S2-3: The suspension D and the solution E are mixed, stirred at 70-80° C. for 1.5 h, washed with deionized water and anhydrous ethanol, and freeze-dried in a freeze dryer to obtain the modified cellulose nanocrystals.

3. The environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating according to claim 1, characterized in that: The dispersant is one of polyethylene glycol and polypropylene glycol.

4. The environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating according to claim 1, characterized in that: The cross-linking agent is one or more of silane coupling agents KH550, KH560 and KH570.

5. The environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in S1-2 is 6M.

6. The environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating according to claim 1, characterized in that: The dropping speed of solution B in S1-3 is 1 mL / min.

7. The environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating according to claim 1, characterized in that: The freeze-drying temperature of the freeze dryer in S2-3 is -30°C, and the freeze-drying time is 12 hours.

8. The environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating according to claim 1, characterized in that: The film-forming aid is alcohol ester 12.

9. A method for preparing an environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating as claimed in claims 1 to 8, characterized in that: The specific steps of the preparation method are as follows: S9-1: According to the formula, the aqueous polyurethane emulsion, modified cellulose nanocrystals, composite filler, dispersant, crosslinking agent and film-forming aid were mixed for 30 minutes to obtain a coating; S9-2: The steel pipe is added to a 75% by mass ethanol solution and ultrasonicated for 20 minutes, placed in a 60°C vacuum drying oven for 12 hours, and then the surface of the steel pipe is subjected to high-energy shot peening to nano-crystallize the surface, thereby obtaining a pretreated steel pipe; S9-3: Spin-coat the coating on the inside of the pretreated steel pipe, and obtain the coating after drying.

10. An application of the environmentally friendly, chemically resistant, high-pressure hydrogen transport and storage coating as claimed in claims 1 to 9, characterized in that: The coating can be applied to hydrogen transmission pipelines and hydrogen storage cylinders.

Citation Information

Patent Citations

  • Hydrogen-resistant composite coating and preparation method thereof

    CN115704090A

  • Hydrogen-permeation-resistant coating, preparation method thereof and application of hydrogen-permeation-resistant coating on stainless steel surface

    CN117887293A

  • Hydrogen gas barrier film and manufacturing method thereof

    JP2018002885A

Cited By

  • Environmentally friendly chemical-resistant high-pressure hydrogen transmission and storage coating and preparation method therefor

    WO2026137908A1